2014
DOI: 10.1111/vop.12228
|View full text |Cite
|
Sign up to set email alerts
|

Corneal grafting for the treatment of feline corneal sequestrum: a retrospective study of 18 eyes (13 cats)

Abstract: Keratoplasty is an effective surgical treatment for FCS. The donor tissue provides excellent tectonic support to the affected corneas, with good visual and cosmetic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 31 publications
(66 reference statements)
5
69
1
2
Order By: Relevance
“…A previous study conducted in cats has reported that tropicamide induce pupil dilation greater than 10 mm for more than 2 hours . Therefore, we aimed to compare the maximal pupil diameter (MPD) reached in the treatments groups with the MPD reached by a topical cholinergic agent that is commonly prescribed for intraocular procedures . In humans and rabbits, the intracameral injection of 0.2‐0.3 mL of 1% lidocaine provided similar or even superior pupil dilation when compared to that obtained with the use of topical mydriatics.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…A previous study conducted in cats has reported that tropicamide induce pupil dilation greater than 10 mm for more than 2 hours . Therefore, we aimed to compare the maximal pupil diameter (MPD) reached in the treatments groups with the MPD reached by a topical cholinergic agent that is commonly prescribed for intraocular procedures . In humans and rabbits, the intracameral injection of 0.2‐0.3 mL of 1% lidocaine provided similar or even superior pupil dilation when compared to that obtained with the use of topical mydriatics.…”
Section: Discussionmentioning
confidence: 95%
“…The ideal protocol for pupil dilation should induce fast, intense, and stable mydriasis with a duration of at least 2 to 3 hours, while minimizing adverse effects . Topical mydriatic eyedrops are currently the standard method for routine pupil dilation in cats that must undergo corneal and intraocular surgeries . The main disadvantages of mydriatic eyedrops are related to delayed local effect .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PK is not presently routinely performed in dogs and uncommonly used for visual rehabilitation. Most corneal transplants are applied as tectonic grafts in dogs …”
Section: Introductionmentioning
confidence: 99%